Dynamical gluon masses in perturbative calculations at loop level: towards an effective loop expansion for quantum chromodynamics - Machado, Fátima Araujo [UNESP] (2014)
This thesis is based on part of the work done during the Ph.D., and it concerns the two distinguished domains of Quantum Chromodynamics (QCD) at zero temperature: the low-energy, confined domain, and the high-energy, asymptotically free one. Aiming to bridge the gap between them, and inspired by suggested improvements of the QCD perturbative series, this work investigates a proposal for an improved perturbative expansion, as a method to be applicable to QCD phenomenology, as well as to nonperturbative studies. The proposal consists in an effective-loop expansion - a hybrid between Schwinger- Dyson equations and usual loop expansions, making use of the latter's framework, yet dressing certain quantities in order to account for their complete behavior inside loops. The thesis describes the main efforts on this matter, in its application to correlation functions - the gluon and ghost propagators, in particular, as a preliminary step preceding further applications. After dealing with issues as transversality of the gluon self-energy and renormalizability within the method, the present form of the effective-loop expansion contains dynamically massive gluons and an effective running charge, besides the possible dressing of the three-gluon vertex. Within this formulation, reasonable qualitative results were obtained for achieving the complete, nonperturbative behavior of the ghost and gluon propagators, and comparison with lattice is analyzed. Readily achievable and longer term prospects are also discussed